Ceremonial Storytelling Ritual and Narrative in Post-9/11 US Wars - Usbeck, Frank (American Culture, 2019)
US society has controversially debated civil-military relationships and war trauma since the Vietnam War. Civic activists today promote Indigenous warrior traditions as role models for non-Native veteran reintegration and health care. They particularly stress the role of ritual and narrative for civil-military negotiations of war experience and for trauma therapy. Applying a cultural-comparative lens, this book reads non-Native soldiers' and veterans' life writing from post-9/11 wars as «ceremonial storytelling.» It analyzes activist academic texts, «milblogs» written in the war zone, as well as «homecoming scenarios.» Soldiers' and veterans' interactions with civilians constitute jointly constructed, narrative civic rituals that discuss the meaning of war experience and homecoming.